IMPLEMENTASI FILSAFAT IDEALISME MELALUI PENDIDIKAN SEKOLAH DASAR - Idawati; Abdul Khaliq Ahmad; Nurfadillah Aprilia; Mirna Sentya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Education is a conscious human effort to develop individual potential to be able to adapt to changing times. In this context, the philosophy of idealism plays an important role in forming educational goals that focus on character and moral development. Idealism, popularized by Plato, emphasizes that true reality is not just material, but is composed of ideas and concepts. Through this approach, education is expected to produce individuals who are not only intellectually superior but also have moral and spiritual integrity. This research uses literature research methods to analyze literature related to the philosophy of idealism and its impact on education. According to research results, idealistic education aims to develop balanced humans who can contribute to society and have a harmonious relationship with God.